The competitiveness of Arab Countries exports (Analytical study of the competitiveness index in some Arab countries) (Al-Mansour Journal, 2022)
Because of the developing globalization, the gradual reduction of traditional barriers, the focus on quality, and the accession, National Arab Industry has lost a lot of protective and supportive measures. The markets of this industry exhibit various manufactured imported goods because of the insufficiency of local product and its decreasing ability concerning international competitiveness.The paper tries to analyze the competitive situation in some Arab Countries through analyzing a number of competitive indicators, taking into account the data of certain period in connection to Arab Countries. But the unavailability of data for all Arab countries in international sources has led to limit the study to the available data of some years.The paper concludes that the performance of the Arab Countries in current Competitiveness is much better than their performance in the underling competitiveness because of the application of strict economic stabilization policies.
Keywords: Competitiveness; Current and Potential Competitiveness Index; Concentration and Diversity; Trade Efficiency Index